186k views
5 votes
Match the expressions given in words with their values when m=6.

15
21
3
42
2
the sum of mand 3 divided by the
difference of m minus 3
the sum of 3 times mand 4 times m
the difference of the product of 3 and m
minus the quotient of m divided by 2
the quotient of 6 divided by the
difference of m minus 3

1 Answer

4 votes

Answer:

Value of expression 1 = 3

Value of expression 2 = 42

Value of expression 3 = 15

Value of expression 4 = 2

Explanation:

Expression 1 : the sum of m and 3 divided by the difference of m minus 3

Expression 1
: (m+3)/(m-3)

Substitute m = 6

So, value of expression 1=
(6+3)/(6-3)=3

Expression 2 : the sum of 3 times m and 4 times m

Expression 2: 3m+4m

Substitute m = 6

So, value of expression 2=3m+4m=3(6)+4(6)=42

Expression 3 : the difference of the product of 3 and m minus the quotient of m divided by 2

Expression 3:
3m-(m)/(2)

Substitute m = 6

So, value of expression 2=
3m-(m)/(2)=3(6)-(6)/(2)=15

Expression 4 :the quotient of 6 divided by the difference of m minus 3

Expression 4:
(6)/(m-3)

Substitute m = 6

So, value of expression 4=
(6)/(m-3)=(6)/(6-3)=2

User PeterVermont
by
4.6k points